2003
DOI: 10.1073/pnas.1635116100
|View full text |Cite
|
Sign up to set email alerts
|

An emotion-induced retrograde amnesia in humans is amygdala- and β-adrenergic-dependent

Abstract: The influence of emotion on human memory is associated with two contradictory effects in the form of either emotion-induced enhancements or decrements in memory. In a series of experiments involving single word presentation, we show that enhanced memory for emotional words is strongly coupled to decrements in memory for items preceding the emotional stimulus, an effect that is more pronounced in women. These memory effects would appear to depend on a common neurobiological substrate, in that enhancements and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
335
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(382 citation statements)
references
References 32 publications
34
335
13
Order By: Relevance
“…Previous work has found that when emotional distracters and the target stimuli are presently serially in a rapid visual stream, emotional distracters will cause significant behavioral interference ,Mitchell et al, 2006,Strange et al, 2003. However, this was not found in the current study.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Previous work has found that when emotional distracters and the target stimuli are presently serially in a rapid visual stream, emotional distracters will cause significant behavioral interference ,Mitchell et al, 2006,Strange et al, 2003. However, this was not found in the current study.…”
Section: Discussioncontrasting
confidence: 89%
“…Etkin et al, 2006;Haas et al, 2006). However, this was not an emotional Stroop paradigm and previous work has demonstrated that emotional distracters can cause representational interference ,Erthal et al, 2005Harris & Pashler, 2004;Mitchell et al, 2006,Okon-Singer et al, 2007,Strange et al, 2003. Of course, in many of these studies the emotional distracters have been visual images ,Erthal et al, 2005Mitchell et al, 2006; though see Harris & Pashler, 2004;Strange et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to subjective ratings of arousal collected for this study, it also appears that semantic relationships can significantly increase arousal ratings (Figure 4a), perhaps further contributing to episodic free-recall. The finding by Strange et al (2003), demonstrating that the recall of the emotional word inhibited rather than facilitated the recall of the previous neutral word, appear to be in stark contrast to the above conclusion. However, the control words used by Strange et al (2003) all shared a semantic category, while the emotional oddball words shared only a weak semantic relationship to the preceding neutral words and had no incongruent perceptual characteristic.…”
Section: Discussioncontrasting
confidence: 60%
“…Oddball studies that serially present standard stimuli and randomly insert oddballs have previously been used to demonstrate enhanced episodic free-recall for emotional oddballs, and disrupted consolidation for neutral stimuli preceding an emotional oddball (Hurlemann et al, 2005;Miu et al, 2005;Strange et al, 2003;Tulving, 1969). Increased encoding and successful remembering of the emotionally negative oddball predicts the disrupted consolidation and subsequent forgetting of the preceding neutral stimulus (Strange et al, 2003). Due to the facilitative role of semantic memory in episodic free-recall, and naturalistic accounts of increased memory for the moments preceding traumatic events (Ehlers et al, 2004(Ehlers et al, , 2002, we will examine whether a semantic relationship between an oddball and preceding stimuli can reverse disrupted consolidation and be modulated by negative emotion, resulting in greater episodic free-recall.…”
Section: Introductionmentioning
confidence: 99%